Questionnaire Use and Development in Health Research - Malcolm Koo; Shih-Wei Yang (Encyclopedia, 2025)
A questionnaire is a structured instrument used in health research to systematically collect data on perceptions, behaviors, and health outcomes. It serves as a fundamental tool for capturing patient-reported outcomes, evaluating treatment effectiveness, and monitoring public health trends. Questionnaires can be administered in various formats, including paper-based, digital, or interactive systems, and must be carefully designed to ensure reliability, validity, and minimal bias. While validated questionnaires facilitate cross-study comparability, new instruments may be needed to address emerging health concerns or specific cultural contexts. Adhering to best practices in survey methodology allows researchers to maximize the utility of questionnaires, ensuring accurate, reproducible, and ethically sound health research.